Mapping of regional potential groundwater springs using Logistic Regression statistical method - Zandi, J.; Ghazvinei, P.T.; Hashim, Roslan; Yusof, K.B.W.; Ariffin, J.; Motamedi, S. (Interperiodica, 2016)
Increasing demand for fresh water extraction in the semi-arid regions necessitates the exploration of groundwater spring potential areas notwithstanding the importance of both conservation and management aspects for planning development. Potential map of groundwater springs reduces the costs of horizontal well drilling that provides useful tool for engineers to locate probable region for groundwater existence. The objective of this study is to establish a model of the potential map of groundwater spring occurrences. A statistical and probabilistic Logistic Regression (LR) model was developed in association with the specified spring location and effective occurrence factors. The most statistically significant effective factors on spring occurrences were selected to zone groundwater spring potential areas. The proposed model was evaluated statistically. Results showed a satisfactory prediction for the proposed model. The outcome of this study facilitates the low-cost utilization of groundwater resources when policy makers need strategic development planning.